Novel test rig to demonstrate a multi functional flap mechanism offering a 2nd degree of freedom - (:unkn) unknown (ICAS, 2024)
Within the consortium for “MovAbles for Next generaTion Aircrafts” (MANTA) in the frame of the Clean Sky 2 program, an innovative Multi-Functional Flap Mechanism (MFFM) is being developed, which enhances the effectiveness and expands the functionality of aircraft’s control surfaces by integration of a second degree of freedom (DOF) in the flap kinematics. This innovation contributes to the Clean Sky 2 key objectives by minimizing the environmental impact of aviation and reducing CO2 emissions by 3 to 5%. This paper describes the test development, demonstration, virtual testing and result correlation of a simplified yet representative MFFM using a novel test rig at Royal NLR. The objective is to demonstrate that the MFFM can rotate at a speed of 60 degrees per second in retracted, take-off, and landing flap positions, under conditions of intact operation, actuator failure, and jamming scenario’s. During the rotation, aerodynamic loads will be simulated using mechanical springs and masses, and wing bending will be simulated through hydraulic actuation of the wing attachments. A separate flexible tube test demonstrates the durability of a flexible hydraulic tube attached to the MFFM. The tube must be able to withstand the aircraft's operational life under maximum operating pressure without rupturing or breaking, even under cold temperature and contaminated conditions. This paper provides the design of the tube demonstration set-up as well as the durability results.